"That Is Film, Not Simply Footage Which Lacks a Soul"—Jorge Prelorán and Ethnographic Cinema. Issue 5 (20th October 2019) - Campo, Javier
Abstract : This article will analyze Jorge Prelorán's texts, as well as published interviews, so as to identify notions and points of view that he elaborated about the craft of cinematography. Special emphasis will be placed on his initial experience at the UCLA Colloquium on Ethnographic Film (1968), and later in the Ethnographic Film Program of the same institution. His reflections accompany his films unfailingly; his professional career as a university professor and researcher, and his role as a trainer of new directors, links his discursive strategies with the will to expand his field of pedagogical and artistic action.